PERAN KURIKULUM KULLIYATUL MU’ALLIMIN AL-ISLAMIYAH (KMI) GONTOR 9 DAN DISIPLIN PONDOK DALAM MENUMBUHKEMBANGKAN KARAKTER SANTRI - Abdul Mufid Setia Budi; Apud Apud (Tarbawi, 2019)
This study aims to describe the curriculum of Kulliyatul Muallimin al-Islamiyyah Gontor and cottage discipline in developing the santri character, which includes: the application of a curriculum developed in the modern Gontor boarding school, the application of cottage discipline during santri living in dormitory environments, and the formation of santri characters as a result of the implementation of the KMI curriculum and cottage discipline. This study is a field research with a qualitative-descriptive approach. The results showed that (1) Kont Gontor 9 curriculum is an integration between the curriculum of scientific competence and character formation that is implemented in the totality of santri's life for 24 hours, (2) Gontor 9 cottage discipline is a standard rule of santri activity while staying in the cottage which includes time discipline, place discipline, activity discipline, self discipline, and (3) KMI curriculum in this case there is a written curriculum and hidden curriculum which acts as a guideline in the process of developing the character of santri through curricular, cochurricular, extracurricular programs designed in 24-hour activities. Keywords. Kulliyatul Mu'allimin Al-Islamiyah curriculum, discipline, character.